Your Home in Cross Stitch - Thompson, Barbara and Green, Ann (Newton Abbot David & Charles Book, 1994)
The home has traditionally formed the inspiration and central theme for samplers worked with cross-stitch. This book takes both beginners and experienced stitchers a stage further, with instructions for creating original cross-stitch pictures of their own homes, both inside and out
Include Colour Illustrations and Index
Keywords: Cross-stitch -- Dwellings in art